DIRECTIONS OF PERFECTION OF MANAGEMENT OF FOREIGN ECONOMIC ACTIVITIES OF THE ORGANIZATION - Yuri A. Navradov (Вестник Северо-Кавказского федерального университета)
Given the problems of organizations, involved in foreign economic activities, as well as the state control in this field, suggests some solutions.